2016
DOI: 10.1071/fp15283
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, light energy partitioning, and photoprotection in the shade-demanding species Panax notoginseng under high and low level of growth irradiance

Abstract: Partitioning of light energy into several pathways and its relation to photosynthesis were examined in a shade-demanding species Panax notoginseng (Burkill) F.H.Chen ex C.Y.Wu & K.M.Feng grown along a light gradient. In fully light-induced leaves, the actual efficiency of PSII photochemistry (ΔF/Fmʹ), electron transport rate (ETR), non-photochemical quenching (NPQ) and photochemical quenching (qP) were lower in low-light-grown plants; this was also the case in fully dark-adapted leaves under a simulated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 58 publications
1
30
0
1
Order By: Relevance
“…Previous studies have reported morphological changes of plants in response to LL stress, such as thinner leaves (Fu et al 2014) and lower biomass (Gustafsson and Boström 2013). Another study reported that LL could decrease the biosynthesis of photosynthetic pigments (Zhang et al 2018) and reduce the chlorophyll (Chl) fluorescence parameters (Chen et al 2016). Under LL stress conditions, enzymes components of Calvin-Benson cycle, particularly Rubisco, exhibited an apparent tendency of diminishing activities leading to lower CO2 assimilation rate, eventually resulting in prominent depression of plant growth (Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported morphological changes of plants in response to LL stress, such as thinner leaves (Fu et al 2014) and lower biomass (Gustafsson and Boström 2013). Another study reported that LL could decrease the biosynthesis of photosynthetic pigments (Zhang et al 2018) and reduce the chlorophyll (Chl) fluorescence parameters (Chen et al 2016). Under LL stress conditions, enzymes components of Calvin-Benson cycle, particularly Rubisco, exhibited an apparent tendency of diminishing activities leading to lower CO2 assimilation rate, eventually resulting in prominent depression of plant growth (Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we sequenced the chloroplast and mitochondrial genomes of three diploid and three tetraploid Panax species along with five varieties of the P. bipinnatifidus species complex. All these Panax species are shade-demanding perennial herbs and inhabit the cool shaded habitats (Liu and Xiao, 1992 ; Chen et al, 2014 , 2016 ). In the case of the agro-economically important species P. ginseng , while cultivated ginseng harbored similar level of nucleotide diversity compared to the wild ginseng in the nuclear genome, obviously lower sequence polymorphisms were found in the chloroplast genome of cultivated ginseng (Li et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is a time lag between onset of a sunfleck to achievement of PNmax (Allen and Pearcy 2000, Bai et al 2008, Martins et al 2013, Chen et al 2016. This time lag may lead to excess excited electrons, at least temporarily, during photosynthetic induction (Watling et al 1997, Tausz et al 2005.…”
Section: Rapid Activation Of Npq In Initial Inductionmentioning
confidence: 98%
“…Plant leaves have various photoprotective mechanisms to cope with excess light energy from strong sunflecks, such as avoiding exposure to light, nonphotochemical quenching (NPQ), and photorespiratory pathways (Watling et al 1997, Tausz et al 2005, Huang et al 2015, Chen et al 2016, Yamori 2016. The rapid activation of NPQ largely dissipates the excess light energy absorbed during sunflecks (Tausz et al 2005, Watling et al 1997.…”
Section: Introductionmentioning
confidence: 99%